A Decade of Social Media Education: Student Expectations and Reactions From Alumni Professionals. (November 2022) - Childers, Courtney C.
The increased emphasis on targeting audiences via digital and social media channels necessitates the updating of traditional advertising curriculum. Academic courses specializing in social media strategy, analytics, and campaigns are vital to the advertising educational landscape as we strive to best prepare students for future employment. Phase 1 of this research draws upon key insights associated with a random sample of enrolled student surveys from a Social Media course taught from spring 2011 to fall 2019 ( n = 230). Phase 2 added 12 in-depth interviews with alumni of the course and current U.S. advertising professionals who identify social media as a core function of client business. Implications for how to best prepare future advertising students for a career in social media via advertising curricula are provided.